2021
DOI: 10.1111/ijpo.12850
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance and psychosocial functioning in European schoolchildren: The role of cardiorespiratory fitness and weight status

Abstract: Summary Background Whether a high cardiorespiratory fitness (CRF) can attenuate the potential detrimental effect of childhood obesity on academic performance and particularly psychosocial functioning remains unclear. Objectives To analyse the academic performance/psychosocial functioning of schoolchildren attending to their CRF and weight status. Methods 470 schoolchildren (46% girls, 7 ± 0 years) from 20 schools in five European countries were categorized as (i) having overweight/obesity (n = 113) or normal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For instance, Castro-Piñero et al 13 found in their study including children aged 6-10 years that 37% of boys and 70% of girls met the criterion-referenced standards for CRF (i.e., 42 and 35 ml/kg/min cutoff points in boys and girls, respectively). Similarly, Valenzuela et al 12 found in their study that the 60% of the European children analyzed (including Spanish children) met these same CRF criterion-referenced standards.It has been suggested that a balanced diet (e.g., low in SSBs) would have major physical fitness benefits during childhood and adolescence 14 . Supporting this notion, CRF has been found to be related to lower SSB consumption in adolescents (only statistically significant in girls) 15 .…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…For instance, Castro-Piñero et al 13 found in their study including children aged 6-10 years that 37% of boys and 70% of girls met the criterion-referenced standards for CRF (i.e., 42 and 35 ml/kg/min cutoff points in boys and girls, respectively). Similarly, Valenzuela et al 12 found in their study that the 60% of the European children analyzed (including Spanish children) met these same CRF criterion-referenced standards.It has been suggested that a balanced diet (e.g., low in SSBs) would have major physical fitness benefits during childhood and adolescence 14 . Supporting this notion, CRF has been found to be related to lower SSB consumption in adolescents (only statistically significant in girls) 15 .…”
mentioning
confidence: 61%
“…For instance, Castro-Piñero et al 13 found in their study including children aged 6-10 years that 37% of boys and 70% of girls met the criterion-referenced standards for CRF (i.e., 42 and 35 ml/kg/min cutoff points in boys and girls, respectively). Similarly, Valenzuela et al 12 found in their study that the 60% of the European children analyzed (including Spanish children) met these same CRF criterion-referenced standards.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…33 Interestingly, no differences between responders and non-responders were observed neither at baseline nor in the change induced by the intervention for other variables such as body mass index, physical activity levels, or cardiorespiratory fitness, which have been traditionally thought to mediate, at least partially, exercise benefits on cognitive performance and psychosocial functioning in children. 34,35 Thus, other variables apart from the abovementioned ones might explain the benefits observed with the present intervention, although research is warranted to confirm whether additional improvements might have been observed with more demanding interventions (e.g., interventions focused on improving cardiorespiratory fitness), particularly given that in the present ancillary analysis the intervention was implemented during the two hours of physical education, without adding any extra hours of physical activity.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, no differences between responders and non‐responders were observed neither at baseline nor in the change induced by the intervention for other variables such as body mass index, physical activity levels, or cardiorespiratory fitness, which have been traditionally thought to mediate, at least partially, exercise benefits on cognitive performance and psychosocial functioning in children 34,35 …”
Section: Discussionmentioning
confidence: 95%